LCL filter design based on ripple current minimization approach for grid-connected inverter application - Yaakub, Muhamad Faizal; Mohd Radzi, Mohd Amran; Asri, Maaspaliza; Shafie, Suhaidi; Azis, Norhafiz; Mohd Noh, Faridah Hanim (IEEE, 2021)
The fast-growing demand for renewable energy has stimulated the rapid development of semiconductor devices and power electronic converter technologies. The gridconnected inverter has turn out to be normal in any distributed generation system. LCL filter is commonly adopted to interconnect an inverter to a utility grid, owing to its parametric performance. However, the common issue regarding resonance frequency and design constraints complexity remains unsolved entirely. In this paper, a simple LCL filter design to address these issues is proposed. A ripple current minimization approach is adopted in the systematic design process to determine optimized reactive components’ value and mitigate its resonance frequency. Design feasibility is simulated in the Matlab/Simulink environment and extensive experimental work was carried out to validated the results against the IEC61000-3- 2 standards.